Neurotrophic factors in patients with primary open-angle glaucoma and age-related cataract. Part 3. Glial-derived neurotrophic factor - A.A. Troshina; A.A. Shpak; A.B. Guekht; T.A. Druzhkova; N.V. Gulyaeva (Офтальмохирургия)
Purpose. To evaluate content of glial-derived neurotrophic factor (GDNF) in the aqueous humor (AH), lacrimal fluid (LF), and blood serum (BS) in patients with primary open-angle glaucoma (POAG) and age-related cataract. Material and methods. A comprehensive examination of a group of patients with POAG in combination with age-related cataract was carried out. As a comparison group, previously examined patients with age-related cataract were taken. The content of GDNF in the LF, AH and BS was studied in all patients. Collection of stimulated LF was performed with a pipette dispenser on the day preceding surgery; the AH and BS were sampled during the phacoemulsification of a cataract. The concentration of GDNF was measured using an enzyme immunoassay. Results. At the early stages of POAG (stages 1–2 according to classification by Mills et al, 2006) there was a significant decrease in the level of GDNF in all studied biological fluids, especially pronounced in the AH and LF – about 2 times (P <0.001); the decrease of GDNF in the BS was less than 20% (P <0.05). In stages 3-4, the GDNF levels consistently increased; the levels of GDNF in the LF and AH remained significantly reduced in comparison with patients without glaucoma. An inverse correlation with the perimetric index VFI was found for the content of GDNF in LF and BS; a direct correlation was found between the GDNF levels in BS and AH. Conclusion. In patients with POAG, a significant decrease of GDNF content in the LF, AH and BS was revealed, especially in the early stages of the disease. In subsequent stages, reduction of GDNF levels in the AH and LF was consistently less significant. With the disease progression, there is a gradual increase in the concentration of GDNF in the AH and LF; nevertheless, the level of GDNF in these fluids remains significantly reduced compared to patients without glaucoma. An inverse correlation with the perimetric index VFI was found for the content of GDNF in LF and BS, as well as a direct correlation of GDNF levels in the BS and AH.